Depreciación de las propiedades de la Asociación de Producción Agrícola 6 de octubre ASOPROAGROC, en el periodo 2022, del cantón Vinces Parroquia Antonio Sotomayor Recinto Junquillo. - Mendoza Guerrero, Carmen Dayana (2023)
The following study addressed problems related to the property, plant and equipment assets account existing in the agricultural production association 6 de October ASOPROAGROC during the period 2022. The problem was directly related to the need to address the issue of wear and tear of assets within the association and to understand how they are replaced at the end of their useful life. The justification is based on the importance of complying with all relevant regulations when depreciating an asset, considering the management of IAS 16 within this process. The main objective of the study was to value the association's assets and quantify their depreciation to establish their fair value. In order to achieve this goal, a mixed methodology was applied, combined with interviews with the association's accounting personnel. The results revealed that there are shortcomings that can be corrected with an adequate implementation of the accounting processes, in addition to establishing that the association should implement the straight-line depreciation method in its processes